Blokade Jantung Total pada Anak - A. Samik Wahab, A. Samik Wahab (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
The diagnosis of complete heart block is based on electrocardiogram. There would be few or even no cases missed if electrocardiograms were made of all slow heart rate infants and children. The history, physical signs, and XÃ¢â¬Â¢ray would lead to the recognition of congenital and acquired complete heart block as an isolated, uncomplicated, anomaly. Incomplete history in healthy asymptomatic older children may cause difficulty in differentiating congenital or acquired origin.The conduction defect is usually discovered accidentally in healthy, asymptomatic children. Adams-Stokes syncopes rarely happen, even in the young. An obstetrician may detect a slow fetal heart rate, in which fetal electrocardiography and echocardiography have diagnostic value. A history of maternal lupus (SLE) or collagen disease or connective tissue disease (CTD) is another-major important diagnostic. The arterial pulse is very slow, the pulse amplitude wide and rhythm regular, The jugular venous pulse is intermittent cannon waves due to independent A waves which are asynchronous with and more rapid than the carotid pulse.The diagnosis is confirmed by electrocardiogram, the P waves and QRS complexes have no constant relation. The QRS duration is normal if the heart beat is initiated high in the His bundle and prolonged if the pacemaker is located below it.The treatment is directed especially to Adams-Stokes syncope. Digitalisation and other anticongestive measures may be indicated if cardiac failure occurs. In patients with recurrent AdamsÃ¢â¬Â¢Stokes attacks, resting ventricular rate of 40 beats per minute or less probably should be paced.The prognosis for congenital and acquired heart block is usually favourable.Key Words: heart block – a-v block – congenital heart disease – acquired heart disease –rheumatic heart disease